Perioperative Blood Loss in South African Primary Hip Arthroplasty Patients - Khattab, Mohamed S.; Moodley, Yoshan (University of Toronto Medical Journal, 2019)
Background: Perioperative blood loss in South African (SA) primary hip arthroplasty patients has not been described. This information could improve patient management during the perioperative period in this setting. Our study objectives were to 1) determine perioperative blood loss in SA primary hip arthroplasty patients, and 2) determine which characteristics are associated with major perioperative blood loss in SA primary hip arthroplasty patients. Methods: This was a retrospective cohort study of 174 patients who underwent primary hip arthroplasty over a 22-month period at the Inkosi Albert Luthuli Hospital, SA. All patients were part of a pre-existing registry. Data for each patient included: Age, gender, anthropometric measurements, comorbidity, orthopaedic variables, laboratory test results, American Society of Anesthesiologists Score, general anaesthesia, duration of surgery, preoperative tranexamic acid, postoperative thromboprophylaxis, and perioperative blood transfusion. Estimated perioperative blood loss (in mL) was calculated using the Gross Equation. Minimum, maximum, mean, and median perioperative blood loss were calculated. Major perioperative blood loss was defined as an estimated perioperative blood loss which was >75th percentile obtained for the study sample. Data were analyzed using appropriate methods. Results: Perioperative blood loss ranged from 10.3 mL to 3041.8 mL. Mean perioperative blood loss was 1103.1 ± 556.2 mL. Median perioperative blood loss was 1008.8 mL, with an interquartile range of 706.2–1357.0 mL. Independent statistical associations were observed between major perioperative blood loss and the following characteristics: chronic obstructive pulmonary disease (OR: 3.01, 95% CI: 1.01–8.95; p=0.048), preoperative tranexamic acid (OR: 0.28, 95% CI: 0.13–0.63; p=0.002), and perioperative blood transfusion (OR: 10.18, 95% CI: 3.53–29.34; p<0.001). Conclusion: The levels of perioperative blood loss observed in our sample of SA primary hip arthroplasty patients are consistent with the range of estimated blood loss reported in the published literature for hip arthroplasty populations in other countries. SA primary hip arthroplasty patients who suffer major perioperative blood loss are more likely to have COPD or require perioperative blood transfusion. Preoperative tranexamic acid was protective against major perioperative blood loss.
Primary Research